Analysis of Development Inequality in Kedungsepur Area - Khoir Akfini Didia (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2018)
The development’s problem faced in Indonesia time by time is inequality as a result from failure of the centralistic system which affected the widening of the gap between rich and poor, urban biased development, imbalance between economic sectors and regional inequality. This study aims to analyze what factors are affect on development inequality in Kedungsepur area and to know did convergence happen in Kedungsepur area. This study uses secondary data from the Central Statistics Agency of Central Java Province and Regional Investment Agency of Central Java Province from 2008 to 2013. The variables of this study are investment, human development index, labor force participation rate, and population. In this study, we used quantitative study methods by using multiple linear regression analysis with Ordinary Least Square method (OLS). The results of this study note that investment did not affect significantly on inequality of Kedungsepur area, HDI affects significantly on inequality of Kedungsepur area, labor force participation rate did not affect significantly on inequality of Kedungsepur area, and population affects significantly on inequality of Kedungsepur area and then there is convergence process in Kedungsepur area